A Comparative Study on Environment Credit Risk Management of Commercial Banks in the Asia‐Pacific Region. (10th September 2013) - Mengze, Hu; Wei, Li
Abstract: Environmental credit risk management (ECRM) is significant in the reduction of environmental risks for banks, the expansion of economic instruments for governmental environmental management and the promotion of green growth in the Asia‐Pacific region. In this paper, we reconstructed an evaluation criterion with 32 indicators for ECRM performance of banks, and selected 120 sample banks from 12 countries in this region for a comparative study. We conducted a gap analysis among banks with systematic ECRM and those with preliminary ECRM, suggesting that five indicators need to be improved by the former and 12 indicators caused gaps of the latter. We found banks in different countries with different ECRM performance levels: the Canadian, US and Japanese banks performed the best; the banks from Australia, Republic of Korea, China and Thailand had modest performance and the banks from the other five countries had a low level of performance. The influential factors of policy, voluntary code and green income incentive for banks' ECRM performance are discussed with the results of a correspondence analysis graph and policy practice in several representative countries. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment.